(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article represents a system of teaching approaches and means used for improving senior pupils’ comprehension and skills in using phraseology units defying nonverbal communication. This research is also focused on emphasizing the nonlinguistic principle of vocabulary learning which uncovers the educational potential of idioms. The paper reveals linguistic and cultural nature associated with Ukrainian people’s outlook and behavior. Moreover it gives a set of practical tasks commented by the authors and designed to develop the ability to comprehend the semantization processes of idioms with nonverbal component and to increase the efficiency of communicative culture.